Nuclear Strategy and National Security: Points of View - Pranger, Robert J.; Labrie, Roger P. (Washington: American Enterprise Institute for Public Policy Research, 1977)
This volume is designed to present the major arguments in the debate and issues related to it. The debate focused on three topics: An overview of America's changing global role; strategic doctrine; and implications for arms control.
Includes bibliographical references.
ne 17/05/2018
Loans
Keywords: Strategy; Nuclear weapons; United States